Detection of Sesame Allergen Traces with Two PCR Assays - The Challenge to Protect Food-Allergic Consumers - Dimitra Panagiotis Houhoula; Vasilios Belsis; Leonidas Georgopoulos; Virginia Giannou; Vasiliki R. Kyrana; John Tsaknis; Vladimiros P. Lougovois; Stamatios Koussissis (Turkish Journal of Agriculture: Food Science and Technology, 2015)
The purpose of this study was to investigate the possible presence of sesame in commercial foods normally carrying no warning for the allergen, but which may have been subjected to contamination during processing. One hundred units of widely consumed goods with high potential to contain allergenic substances deriving from nuts were analyzed, using sensitive and capable PCR (C-PCR) and Real Time PCR (RT-PCR) methodologies. Of the products examined, 15 (15.0%) declared the presence of sesame, 36 (36.0%) carried no food allergy label, 44 (44.0%) were marked by the phrase “may contain traces of nuts” and 5 (5.0%) carried the indication “may contain sesame traces”. The sesame-positive products detected using the C-PCR method were 15 (100%), 12 (33.3%), 14 (31.8%) and 3 (60%), respectively. Using the RT-PCR technique, positive results were obtained for 15 (100%), 18 (50.0%), 18 (20.5%) and 5 (100%) samples, respectively. The results indicate that the PCR methods applied are highly sensitive and selective, which makes them suitable for the detection of sesame traces in food samples. In addition, they can be useful for monitoring the effectiveness of cleaning processes in the production units of the food industry.